Implementation of the Jigsaw Type Cooperative Model in Increasing Student Learning Interest in Fiqh Subjects at Mts At-Taufiqiyah Bluto in 2024 - Pinasti; Achmad Maulidi (Classroom: Journal of Islamic Education, 2026)
The jigsaw cooperative learning model is a learning model that involves student participation in small groups to interact with each other. In this cooperative learning system, students learn to work together with other members. In this model, students have two responsibilities: they learn for themselves and help fellow group members learn. Interest in learning itself is a drive within a person to participate in a learning activity with full attention and active involvement. This study aims to analyze the implementation of the Jigsaw model in increasing student interest in learning in the subject of Fiqh. In addition, this study also identifies supporting and inhibiting factors in the implementation of this model and its impact on student engagement in learning. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The data obtained were analyzed using data reduction techniques, data presentation, and drawing conclusions to obtain a clear picture of the effectiveness of the Jigsaw model in increasing student interest in learning. The results of the study indicate that the jigsaw cooperative learning model is effective in increasing student interest in learning in the subject of Fiqh. With a fun and interactive learning atmosphere, this model not only helps students master the material but also develops social skills and self-confidence. This model helps previously passive students become more engaged in the learning process. Furthermore, the classroom atmosphere becomes more dynamic and enjoyable, so students don't get bored while learning the material. Supporting factors include infrastructure, such as comfortable, clean, and spacious classrooms that support group discussions in the jigsaw model. If classrooms are cramped or unconducive, the learning process can be disrupted, and books are also available. Obstacles include students' lack of enthusiasm and limited time for learning.